Green Products and Electronic Word of Mouth: A Study Special Reference with Significance of Environmental Concern, Knowledge and Consciousness - Rajalakshmi, A. R.; Jayakani, S.; Shanmugam, Harihara; Ramakrishnan, P.R. (Indian Journal of Information Sources and Services, 2024)
The report as decorated in the literature, In the contemporary setting, green products that are produced in an ecologically responsible manner are getting greater attention. The cause of the concentration of people around these items because of environmental interests such as conserving water; protecting natural resources and health consciousness. The present study aims to investigate the electronic word of mouth (e-wom) and green products purchasing connection, the study also looks into the relationship that is not direct through the attitude towards environmental concern, environmental knowledge, and environmental consciousness. The think comprises of 235 customers as respondents. The female respondents are a larger part of this inquiry. The ages of those overviewed were underneath 25 a long time to over 55 a long time. Headed To gauge e-wom influence, five indicators and to assess attitude towards environmental concern, environmental knowledge, and environmental consciousness eight indicators have been used. Respondents were asked to consider and provide details about the green items they had purchased in the previous months to gauge the regularity of their purchases. Additionally, the possibility of buying green items is indicated by the assessment of purchasing willingness for green products. According to the study, e-wom has a direct impact on Green product Purchasing, and also indirectly through environmental concern, environmental knowledge, and environmental consciousness.